2018
DOI: 10.20448/journal.501.2018.52.183.190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Population, GDP and Energy Consumption on Carbon Emissions: Evidence from Pakistan Using an Analytic Tool IPAT

Abstract: This study examines the relationship between CO2 emission, economic growth, population and energy consumption in Pakistan during period of 1975-2016. The study evaluates IPAT (Impact of CO2 x Population x Affluence x Technology) hypothesis where CO2 emission is influence by high population growth, economic growth, and technology. The study use ARDL bounds testing approach to estimate short and long run elasticities. The results confirm that population growth and energy demand both increase the CO2 emission, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Accordingly, a 1% increase in urbanisation led to a 0.65% increase in air pollution deaths in the 25th quantile. An increase in urbanisation means an increase in population, and an increase in population leads to carbon dioxide emissions (e.g., Mansoor & Sultana, 2018 This explanation is con rmed with results that were pointed in Table 5 above, where the urbanisation process increases the consumption of fossil fuels and CO 2 emissions.…”
Section: Empirical Results and Discussionsupporting
confidence: 66%
“…Accordingly, a 1% increase in urbanisation led to a 0.65% increase in air pollution deaths in the 25th quantile. An increase in urbanisation means an increase in population, and an increase in population leads to carbon dioxide emissions (e.g., Mansoor & Sultana, 2018 This explanation is con rmed with results that were pointed in Table 5 above, where the urbanisation process increases the consumption of fossil fuels and CO 2 emissions.…”
Section: Empirical Results and Discussionsupporting
confidence: 66%
“…In the present research, the sample analysis is finished by utilizing two renowned statistical programming software which is the SmartPLS Version 3.2.8 (Ringle et al, 2015) that by a wide range in Pearson's Correlation examination ought to underneath 0.90. Along these lines, affirm the nonappearance of multicollinearity among the factors (Hair et al, 2013;Frooghi et al, 2015;Mansoor and Sultana, 2018).…”
Section: Data Analysis and Interpretationmentioning
confidence: 79%
“…Also in Pakistan Meo et al (2018) apply ARDL bound test found that there is asymmetries relationship between inflation, unemployment and poverty. Bala, Ayatu, and Maijamaa (2020) and Mansoor (2018) found that population growth has direct impact on energy generation and demand in Nigeria and Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%